Giovanni Meo-Zilio y Silvia Mejía, Diccionario de gestos: España e Hispanoamérica. T. 1: A-H. T. 2: I-Z. Instituto Caro y Cuervo, Bogotá, 1980-1983; 190, 235 pp., 246 fotografías. - Smith Stark, Thomas C. (El Colegio de México, 1990)
Se reseñó el libro: Diccionario de gestos: España e Hispanoamérica. T. 1: A-H. T. 2: I-Z.